2018
DOI: 10.1002/jbm.a.36441
|View full text |Cite
|
Sign up to set email alerts
|

Application of mesenchymal stem cells to enhance non‐union bone fracture healing

Abstract: ECM components include a number of osteoinductive and osteoconductive factors, which are involved in bone fracture healing. In this study, a combination of adipose derived mesenchymal stem cells (Ad-MSCs), cancellous bone graft (CBG), and chitosan hydrogel (CHI) was applied to the non-union bone fracture and healing effects were evaluated for the first time. After creation of animal models with non-union fracture in rats, they were randomly classified into seven groups. Radiography at 0, 2, 4, and 8 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 79 publications
(145 reference statements)
1
22
0
1
Order By: Relevance
“…Thus, we hypothesize that a decellularized allogeneic bone tissue-engineered graft enriched with periosteum derived stem cell and growth factors would provide sustained delivery of growth factors, support stem cell delivery, and improve allograft incorporation in a critical-sized rabbit radius defect. The positive effects of MSCs in the treatment of bone fractures have been demonstrated in several studies (39). Similarly, our results demonstrated that MSCs and cortical bone graft with or without platelet growth factors were effective in accelerating non-union bone fracture healing in rabbits.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, we hypothesize that a decellularized allogeneic bone tissue-engineered graft enriched with periosteum derived stem cell and growth factors would provide sustained delivery of growth factors, support stem cell delivery, and improve allograft incorporation in a critical-sized rabbit radius defect. The positive effects of MSCs in the treatment of bone fractures have been demonstrated in several studies (39). Similarly, our results demonstrated that MSCs and cortical bone graft with or without platelet growth factors were effective in accelerating non-union bone fracture healing in rabbits.…”
Section: Discussionsupporting
confidence: 85%
“…Around 5 billion dollars are annually spend in treating bone defects in the US, mainly on bone grafts and implants for bone injuries and other pathologies associated with defective fracture healing, such as non-union [98]. Conventional treatments, including autologous bone grafts, and distraction osteogenesis (DO) have some limitations, such as long immobilization periods, donor site morbidity, muscular atrophy and surgical complications such as infection, pain, or hemorrhage [17,99,100]. Tissue engineering and cell-based therapies have been adopted as alternatives therapies to promote bone repair, and AMSCs have been proposed to treat CSDs [100,101,102,103,104,105,106] and delayed fracture healing and the resulting segmental bone defects [99,107,108,109,110].…”
Section: Application Of Amscs In the Treatment Of Osseous Diseasesmentioning
confidence: 99%
“…Despite advances in fractures treatments, annually, over 5–10% of bone fractures are not able to union [99]. In a study carried out by Ghasroldasht et al, a combination of AMSCs, cancellous bone graft and chitostan hydrogel was applied to non-union bone fractures in rats [99].…”
Section: Application Of Amscs In the Treatment Of Osseous Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Als neuer und vielversprechender Ansatz gilt das mechanische Anfrischen der Pseudarthrose und die anschließende Behandlung mit MSCs. Diese werden mit Trägersubstanzen wie Chitosan-oder Hydroxyapatit-fragmenten vermengt und in die Frakturregion eingebracht [81,82].…”
Section: Mscs Für Die Regeneration Von Knochenunclassified